Role of catheter location on local impedance measurements and clinical outcome with the new direct sense technology in cardiac ablation procedures. (October 2022) - Pesch, E.; Riesinger, L.; Vonderlin, N.; Kupusovic, J.; Koehler, M.; Bruns, F.; Janosi, R.A.; Kochhäuser, S.; Dobrev, D.; Rassaf, T.; Wakili, R.; Siebermair, J.
Abstract: Background: A novel catheter technology (direct sense, DS) enables periprocedural local impedance (LI) measurement for estimation of tissue contact during radiofrequency ablation (RFA) for real-time assessment of lesion generation. This measure reflects specific local myocardial conduction properties in contrast to the established global impedance (GI) using a neutral body electrode. Our study aimed to assess representative LI values for the cardiac chambers, to evaluate LI drop in response to RF delivery and to compare those values to established GI measures in patients undergoing RFA procedures. Methods and Results: Seventy-three patients undergoing RFA with the DS technology were included. Within the cardiac chambers, baseline LI was significantly different, with the highest values in the left atrium (LA 107.5 ± 14.3 Ω; RV 104.6 Ω ± 12.9 Ω; LV 100.7 Ω ± 11.7 Ω, and RA 100.5 Ω ± 13.4 Ω). Baseline LI was positively correlated to the corresponding LI drop during RF delivery (R 2  = 0.26, p = 0.01) representing a promising surrogate of lesion generation. The observed mean LI drop (15.6 ± 9.5 Ω) was threefold higher as GI drop (4.9 ± 7.4 Ω), p < 0.01. We evaluated the clinical outcome in a subgroup of patients undergoing DS-guided pulmonary vein isolation, which was comparable regarding arrhythmia recurrence to a conventional ablation cohort (57 % vs 50 %, p = 0.2). Conclusion: We provide detailed information on LI measures in electrophysiological procedures with significant differences within the cardiac chambers highlighting that RFA-related LI drop can serve as a promising surrogate for real-time assessment of lesion generation. Guiding the electrophysiologist in RFA procedures, this additional information promises to improve safety profile and success rates in the interventional treatment of arrhythmias.